Modifikasi Skala Regulasi Akademik Mahasiswa - Amr, Amr Yazid Pikoli; Huda, Miftahul; Benidha, Benidha Roos Feri Nisa (Journal of Research and Measurement in Psychology: JPPP, 2025)
Abstract The number of academic demands with high intensity can make students experience academic stress. Therefore, in fulfilling these things, students must have strategies that must be arranged to smooth the course of life in lectures so that they can avoid academic stress or other mental illnesses that can hinder their studies. These strategies are framed into academic self-regulation which can be a guide for students to navigate college life well. This study uses a cross-sectional quantitative approach with the academic self-regulation variable as the variable to be studied. The purpose of this study is to modify the academic self-regulation measuring instrument based on Zimmerman's academic self-regulation theory which is adapted to the culture in Indonesia. Psychometric aspect testing was conducted in this study to obtain research data in the form of numbers that will be measured statistically, to produce a conclusion. The results showed that of the 66 final items tested, only 17 items survived until CFA testing. In testing with demographic data, namely MIMIC, Rasch Model, and Dif, the 17 items have been tested and declared reliable and valid.